Anti-Cocaine IgA Rather Than IgG Mediates Vaccine Protection from Cocaine Use - Thomas R. Kosten; Colin N. Haile; Coreen B. Domingo; Elizabeth B. Norton (MDPI AG, 2022)
In developing a vaccine for fentanyl use disorder, we observed that IgA was the best correlate of vaccine-mediated protection from injected drug challenge, rather than IgG or binding affinity. Recent evidence shows that IgA secreting cells line the blood-brain barrier that capture pathogens and could prevent drug antigens from penetrating the brain. We assayed IgA and IgG antibodies from an anti-cocaine vaccine clinical trial and categorized each subject's antibody levels using half-log cut-points for IgA: <1000, <5000, <10,000 and >10,000; and for IgG: <10,000 to >100,000. We compared these antibody groups on urine toxicology in 130 subjects at week 9 after 3 booster vaccinations. We also provided relevant data on benzoylecgonine (BE, cocaine metabolite) from this study's placebo patients. BE urine levels were lowest for the highest IgA category; however, levels did not differ across IgG groups. Our findings linking IgA to protection from cocaine and fentanyl in mice, rats and humans are novel and suggest an increasingly recognized role of IgA in vaccine efficacy.